A música experimental de Gilberto Mendes: contexto e análises - Cruz, João Batista Carvalho de Brito (2017)
The present research studies the experimental phase of Brazilian composer Gilberto Mendes’s work, extracting from such period a few structuring elements of his musical creation, such as the way he interacts with his environment, the semiotical particularities of his works, and their compositional morphology. In order to demonstrate how the work of Mendes during such period is at the same time aesthetically avant-garde (in line with European and north-american vanguards and Brazilian concrete poetry) and communicative, this dissertation investigates the complexity inherent to the musical semiosis under discussion. With that in sight, the research materializes itself in the analysis of three experimental works of the composer’s: nascemorre (1963), Blirium C9 (1964) and Santos Football Music (1969). These analysis were made according to musical semiotics based in Charles S. Peirce’s pragmaticism, since this theoretical-methodological framework enables one to apprehend the complexity of the musical interpretative process in a broad manner, from its production to its fruition